2012
DOI: 10.4238/2012.september.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of sour orange (Citrus aurantium) accessions and their relatives using SSR and SRAP markers

Abstract: ABSTRACT. Citrus production with its many varieties is of importance since it provides economically important products for Turkish exports. Sour orange is a rootstock commonly used for propagating the different scion varieties. Knowledge of the genetic diversity of the rootstock accessions would be useful in order to improve citrus breeding programs. We studied genetic relationships and diversity of 51 accessions of sour orange (Citrus aurantium) and their relatives using SSR (simple sequence repeat) and SRAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This conclusion concerning extremely low/absent genetic diversity is in accordance with previous work [20][21][22][23][24][25][26]49]. Studies using multilocus genotyping with dominant markers found higher diversity than studies using SSR markers [22,24]. Nevertheless, multilocus dominant markers suffer from a lack of repeatability and tend to overestimate the variability [50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This conclusion concerning extremely low/absent genetic diversity is in accordance with previous work [20][21][22][23][24][25][26]49]. Studies using multilocus genotyping with dominant markers found higher diversity than studies using SSR markers [22,24]. Nevertheless, multilocus dominant markers suffer from a lack of repeatability and tend to overestimate the variability [50].…”
Section: Discussionsupporting
confidence: 91%
“…Most studies, mainly using codominant markers such as simple sequence repeat (SSR) markers, concluded that the intervarietal polymorphism was null or very low [20][21][22][23]. Only a few sour orange varieties displayed distinct profiles, such as 'Gou Tou', 'Smooth Flat Seville', 'Tosu', 'Konejime', 'Guo-Kuo-Cheng', 'Goutoucheng' and 'Australian' [22,24,25]. Six cultivars of sour orange were compared using NGS DNA sequences from SSR and indel regions of nuclear and organellar genomes.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol is simple, efficient, and has a high production rate. It has been used successfully in genetic diversity analysis and construction of genetic maps of many plant species [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Because, after coming through by introduction, most Turkish sweet orange accessions originated via mutations from domestic and foreign cultivars. Barkley et al (2006), Jannati et al (2009), Polat et al (2012 and El-Mouei et al (2011) indicated that SSR markers according to other markers were more important tool for cultivar identification, germplasm diversity and phylogenic studying of Citrus. Likewise, our data confirmed that SSR molecular methods are useful tools for the identification of closely accessions.…”
Section: Resultsmentioning
confidence: 99%
“…A number of molecular marker techniques have been used to overcome the limitations of morphological and biochemical markers in citrus genetic classification. Protein, isozymes (Rahman and Nito, 1994), and molecular markers such as restriction fragment length polymorphisms (RFLPs) (Liou et al, 1996), random amplified polymorphic DNA (RAPD) (Machado et al,1996;Baig et al, 2009;Sun et al,2012;Malik et al,2012), sequence-characterized amplified regions (SCARs) (Nicolosi et al, 2000), amplified fragment length polymorphism (AFLP) (Campos et al, 2005), microsatellites simple sequence repeats (SSRs) (Oliveira et al, 2002;Ahmad et al, 2003;Fu et al, 2003;Barkley et al, 2006;Polat, 2009;Jannati et al, 2009;El-Mouei et al, 2011;Uzun et al, 2011;Cristofani-Yaly et al, 2011;Garcίa-Lor et al, 2012;Polat et al, 2012;Kacar et al, 2013;Al-Mouei and Choumane, 2014), inter-simple sequence repeats (ISSRs) (De Pasquale et al, 2006), sequence related amplified polymorphism (SRAP) (Uzun et al, 2009;Uzun et al, 2011;Polat et al, 2012;Kacar et al, 2013), sequencespecific amplified polymorphism (S-SAP) and selectively amplified microsatellite polymorphic loci (SAMPL) have been employed to elucidating genetic diversity, determining parentage, and revealing phylogenetic relationships among various Citrus species. Compared to morphological data, molecular markers provide abundant information, are highly efficient, and are insensitive to environmental factors (Barkley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%